A Electron micrograph of the leaf epidermal structure of legumes - Mamman MUAZU OMEIZA; M, Yusuf; H. A, Muhammed; Z, Abdulmutalib; Salawu, O. N; ABDULHAKEEM S (RADINKA JAYA UTAMA PUBLISHER, 2024)
Our goal was to find morphological features that can help us identify or describe the stomata ontogeny and epidermal structures. Our team got seeds of two types of leguminous plants—Arachis hypogaea L. groundnuts and Vigna subterranean L. bambaranuts—from the Kano State Agricultural and Rural Development Authority and the Yankaba market in Nassarawa, which is in Kano State. The study specifically evaluated the leaf epidermal studies, stomata development (ontogeny), types of stomata, stomata size, pore length, pore width, and stomata index in both the surfaces of the leaves. We conducted ontogenetic studies using safety razor blades on the epidermal layers. We determined the stomata index by studying the type of stomata, the number of stomata, and the number of epidermal cells. We subjected the obtained data to a one-way analysis of variance. All the studied varieties/species exhibited amphistomatic stomata on both surfaces, with a higher density on the lower surface. In SAMNUT 23, we found the paracytic type of stomata, which is perigynous and has an irregular anticlinal cell wall. In Dandakar, we found the tetracyclic type, which is mesogynous and has a pentagonal epidermal cell shape and a slightly straight anticlinal cell wall. Finally, in Bambara nuts, we found the endocytic type, which is polygonal with a curved anticlinal wall and a mesoperigynous ontogeny.